The hidden cinema history: informal distribution of art cinema in Taiwan, 1986-2016 - Lin, Yu-Peng (2019)
This thesis explores the historical informal distribution of art cinema in Taiwan from 1986 to 2016. This historical analysis is conducted through different stages including various media formats and platforms. To examine this area in greater detail, I interviewed seven informal distributors directly linked to Taiwan’s art cinema during this time period. Because there has been limited access to art cinema historically in Taiwan, informal distribution is one of channels for accessing art cinema. From the development of Solar MTV, cinephiles have been able to watch art cinema via advanced technology, including Laser Discs(LDs) and unauthorised Video Home System tapes. Concurrently, informal distributors strengthened access to secure their sales via film magazines. With the advent of unauthorised Digital Video Discs(DVDs) in 2001, informal distribution in Taiwan became transnational across Taiwan’s border with China and operated in tandem with multiplex contradictions such as pricing and practice. Additionally, unauthorised DVDs brought stunning content to cinephiles, which can broaden their watching experience through DVD paratexts. Finally, the online activities of Chinese fansubbing groups present another dimension of informal distribution. In this study, I observed their activities from 2012 to 2015. This research revealed that these groups provide access to alternative art cinema, different from institutional art cinema, which contributes to a more abundant culture of art cinema. In summary, informal distribution plays a significant role historically in Taiwan’s art cinema culture.